The Use of Linoit Website-Based Media as a Digital Portfolio Assessment Tool in German Language Learning at SMAN 1 Kedungwaru - Abdillah, Hamdan Khoiru; Ardiyani, Dewi Kartika (IKIP PGRI Bojonegoro, 2024)
This research aimed to describe students’ activities and responses towards applying of Linoit website-based media as a digital portfolio assessment tool in German language learning. This research was held in class XI-2 MIPA SMAN 1 Kedungwaru. This research used a descriptive qualitative approach. The data used were qualitative data supported by quantitative data. Qualitative data in the form of observation results and quantitative data in the form of questionnaire results were then interpreted into qualitative descriptive. The observation results showed that the use of the website-based media Linoit as a means of digital portfolio assessment was in line with the implementation of the learning design (RPP). The students actively engaged in classroom learning and followed the teacher's instructions to document their learning outcomes and upload them to Linoit as evidence of their digital portfolios. In evaluating the portfolios, the teacher wrote the evaluation results with the help of other media, which were then uploaded to Linoit. The students' responses showed that Linoit could be used as a platform for sharing and learning from each other's learning outcomes uploaded on Linoit. Additionally, the students could easily and quickly manage their learning outcomes through the features available on Linoit. However, Linoit had limitations when used in German language learning, as the essential feature of umlaut characters was not available on the platform. Moreover, the small display of Linoit on mobile phones made it difficult for users to operate its features, requiring additional time for adjustment when using Linoit.